Preparation and property analysis of antioxidant of carbazole derivatives - Zhi-quan Zhang; Bao-wei Zhu; Jing-yu Zhang; Hong Chen (BMC Chemistry, 2024)
Abstract Carbazole derivatives can be used as antioxidants in the lubricating oil industry. The alkylation of carbazole with 2-chloro-2-methylpropane and 2-bromopropane catalyzed by anhydrous aluminum chloride was studied. Initially, 3,6-di-iso-propylcarbazole and 3,6-di-tert-butylcarbazole were using dichloromethane and dibromomethane as solvents at room temperature, respectively. The synthesis conditions were optimized. Subsequently, the effects of reaction time, catalyst dosage, and molar ratio of carbazole to alkylating agent were investigated, and orthogonal experiments were performed. The structures of the carbazole derivatives were characterized by Fourier infrared spectroscopy (FT-IR), mass spectrum (MS) and nuclear magnetic resonance spectroscopy (NMR). The thermal stability of the synthesized carbazole derivatives was investigated by differential scanning calorimetry (DSC). The carbazole derivatives were added into the lubricating oil with a mass fraction of 0.8% and the miscibility, stability and oxidation resistance of the mixed system were evaluated by mechanical stirring and a rotary pressure vessel oxidation test (RPVOT). The DSC results showed that there was good thermal stability for the carbazole derivatives. The mechanical stirring method revealed good solubility and stability for the mixture of oil and carbazole derivatives. The RPVOT results showed that isopropyl carbazole derivatives could increase the oxidation induction period of lubricating oil to 1.39 times, and tert-butyl carbazole derivatives could increase the oxidation induction period of lubricating oil to 1.91 times. The antioxidant effect of tert-butyl carbazole derivatives was better than that of isopropyl carbazole derivatives.